2022
DOI: 10.1101/2022.09.01.506149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparative ‘omics’ approach for prediction of candidate Strongyloides stercoralis diagnostic coproantigens

Abstract: Human infection with the intestinal nematode Strongyloides stercoralis is persistent unless effectively treated, and potentially fatal in immunosuppressed individuals. Epidemiological data are lacking due to inadequate diagnosis. A rapid antigen detection test is a priority for population surveillance, validating cure after treatment, and for screening prior to immunosuppression. We analysed open access 'omics' data sets and used online predictors to identify S. stercoralis proteins that are likely to be pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Diagnosis: Omics approaches were used for discovering a unique antigen specific for diagnosis of S. stercoralis either in serum [55] or stool samples [56] . In the first study, the investigators designed a multi-epitope antigen based on L3Nie.01 and IgG immunoreactive epitopes [55] .…”
Section: Strongyloides Stercoralismentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis: Omics approaches were used for discovering a unique antigen specific for diagnosis of S. stercoralis either in serum [55] or stool samples [56] . In the first study, the investigators designed a multi-epitope antigen based on L3Nie.01 and IgG immunoreactive epitopes [55] .…”
Section: Strongyloides Stercoralismentioning
confidence: 99%
“…In the first study, the investigators designed a multi-epitope antigen based on L3Nie.01 and IgG immunoreactive epitopes [55] . Utilizing phylogenetic comparison, the second study identified five specific coproantigens for diagnosis in stool samples, SCP/TAPS proteins family, transthyretin-like, AChE, aspartic peptidase, and prolyl oligopeptidase [56] .…”
Section: Strongyloides Stercoralismentioning
confidence: 99%